2017
DOI: 10.18632/aging.101239
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic autoinhibition of p21-activated kinase exacerbates synaptic impairments and fronto-dependent behavioral deficits in an animal model of Alzheimer’s disease

Abstract: Defects in p21-activated kinase (PAK) lead to dendritic spine abnormalities and are sufficient to cause cognition impairment. The decrease in PAK in the brain of Alzheimer's disease (AD) patients is suspected to underlie synaptic and dendritic disturbances associated with its clinical expression, particularly with symptoms related to frontal cortex dysfunction. To investigate the role of PAK combined with Aβ and tau pathologies (3xTg-AD mice) in the frontal cortex, we generated a transgenic model of AD with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 99 publications
0
13
0
Order By: Relevance
“…Alzheimer’s disease (AD) is a neurodegenerative disease that occurs in the elderly [ 1 , 2 ]. Its clinical manifestation includes progressive cognitive dysfunction and memory impairment [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer’s disease (AD) is a neurodegenerative disease that occurs in the elderly [ 1 , 2 ]. Its clinical manifestation includes progressive cognitive dysfunction and memory impairment [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 and Supplementary Table 7 ). P21-activated kinase 1, encoded by the PAK1 gene, has been implicated in AD (Zhao et al ., 2006), and recent studies have revealed that inactivation of PAK1 obliterated social recognition without changing amyloid beta (Aβ)/tau pathology, and also exacerbated synaptic impairment and behavioral deficits in mouse models of AD (Arsenault et al ., 2013, Bories et al ., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…AD is associated with changes in synaptic proteins [35,43,[70][71][72][73][74][75], which could have a significant impact at the cellular level. To find if sexes influenced synaptic function at the molecular level in AD, we quantified several proteins in the parietotemporal cortex by Western blot.…”
Section: Transgenic Expression Induced Synaptic Protein Impairmentsmentioning
confidence: 99%